Thermal and Mechanical Characterization of K-Carrageenan/Graphene/Bismuth Oxide Nanocomposites - Cathy B. Escuadro; Gil Nonato C. Santos (Journal of Nanotechnology)
With the health and environmental hazards posed by fossil-based polymer materials, a significant shift toward sustainable, bio-based alternatives has gained prominence. K-carrageenan, derived from red seaweeds, is among the bio-based polymers with promising potential due to its strong film-forming ability. However, their relatively lower thermal and mechanical properties limit their widespread application in the industry. To enhance their properties and stretch its application, k-carrageenan was reinforced with bismuth oxide nanoparticles (Bi2O3 NPs) and graphene nanosheets (GNS). GNS were synthesized using chemical exfoliation and Bi2O3 NPs through the hydrothermal method. This study has fabricated a novel k-carrageenan/GNS/Bi2O3NPs (K-CGBi) nanocomposite films via the facile, eco-friendly, cost-effective solution casting technique. Scanning electron microscopy coupled with elemental dispersive X-ray (SEM-EDX) was used to examine its surface morphology and elemental composition, and attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectroscopy to investigate its chemical composition. Thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) were employed, and their thermal conductivity was also measured to investigate their thermal properties. Morphological analysis confirms the nanofillers were successfully embedded in the matrix, characterized by aggregates of Bi2O3 NP and GNS randomly dispersed at its surface. The inclusion of Bi2O3 NPs and GNS (K-CGBi) further improved the thermal stability of the film samples as demonstrated by its TGA and DSC results, compared to the addition of pure GNS alone (K-CG) and neat k-carrageenan film (K-C). Similarly, its thermal conductivity showed a notable increase at 59% compared to the K-C film and 46% higher than the K-CG film. Furthermore, K-CGBi exhibits improved mechanical properties with a 56% enhancement of tensile strength (TS) compared to neat K-C film. Considering their properties, K-CGBi film can potentially be applied to applications where low to moderate temperature control and mechanical durability are required, such as in packaging, flexible electronics, pharmaceutical and biomedical transport, and cold-chain processing.